PENGARUH ENTREPRENEURIAL TRAITS TERHADAP INTENSI KEWIRAUSAHAAN - Ranto, Dwi Wahyu Pril (Jurnal Bisnis : Teori dan Implementasi, 2017)
This study is aimed at examining the influence of entrepreneurial traits including need for achievement, self-efficacy, and risk taking propensity towards students’ entrepreneurial intention. The population of this study is students of AMA YPK Yogyakarta. This study used purposive sampling in which the criteria of the sample were those who had joined in entrepreneur class. The total numbers of sample processed were 90 students.    Based on the test of hypothesis using multiple regression, it resulted that need for achievement and self-efficacy gave influence toward students’ entrepreneurial intention, while risk taking propensity did not have any influence toward students’ entrepreneurial intention.